2021
DOI: 10.1002/macp.202000372
|View full text |Cite
|
Sign up to set email alerts
|

In Situ AFM Observation of Folded‐Chain Crystallization of a Low‐Molecular‐Weight Isotactic Poly(methyl methacrylate) in a Langmuir Monolayer at the Molecular Level

Abstract: The formation of folded‐chain crystals (FCC) of a low‐molecular‐weight isotactic poly(methyl methacrylate) (it‐PMMA) in a Langmuir monolayer on mica is observed under high humidity by in situ atomic force microscopy at the molecular level. The size of the smallest FCC formed corresponds to the size of a crystal composed of a single chain (single‐chain crystal), and the crystals grow in a stepwise manner with steps comparable to a single chain. The crystal of it‐PMMA is composed of a double‐stranded helix, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Thus, the 2D crystals that formed on the mica correspond to the single-crystal plane of the double-stranded helical crystal, as schematically represented by an ideal chain packing in Figure a. Some irregularity may also occur in the formation of the double-stranded helix and its folding (see Figure 2 in ref ). For each crystal, the molecular weight can be evaluated from the total stem length based on the crystal model and indicated in each image (469, 568, and 596 k).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the 2D crystals that formed on the mica correspond to the single-crystal plane of the double-stranded helical crystal, as schematically represented by an ideal chain packing in Figure a. Some irregularity may also occur in the formation of the double-stranded helix and its folding (see Figure 2 in ref ). For each crystal, the molecular weight can be evaluated from the total stem length based on the crystal model and indicated in each image (469, 568, and 596 k).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, the authors also observed a detailed molecular-level crystallization in which an amorphous single chain was deposited and spread on a crystal-growth plane as new stems to grow the crystal. 41 In previous observations of the crystallization of it-PMMA bulk monolayers, although the stem-level crystallization of folded-chain crystals comprising double-stranded helices could be observed, the individual amorphous chains that did not form thick double-stranded helices in the amorphous region could not be observed at the molecular level, owing to the limited resolution of AFM. We do not know the position at which the crystal nuclei formed in the amorphous chain or how the amorphous chain was incorporated into the crystal.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…By means of in situ X-ray scattering, Su et al reported that the sizes along the long and short axes of crystalline nanograins of poly­(9,9-di- n -octyl-2,7-fluorene) during the primary nucleation stage in a cold crystallization process were about 13 nm and 5 nm, respectively. Via real-time observation of the crystallization process of isotactic PMMA in a monolayer on a substrate via atomic force microscopy, Kumaki et al observed the step growth manner of isotactic PMMA, namely, block by block with a time interval, rather than stem-by-stem growth with a constant rate. The size of the folded chain cluster, which they defined as crystalline nuclei, was independent of the molecular weight.…”
Section: Introductionmentioning
confidence: 99%